2020
DOI: 10.1093/gbe/evaa096
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Insights into Plastid Evolution

Abstract: Abstract The origin of plastids (chloroplasts) by endosymbiosis stands as one of the most important events in the history of eukaryotic life. The genetic, biochemical, and cell biological integration of a cyanobacterial endosymbiont into a heterotrophic host eukaryote approximately a billion years ago paved the way for the evolution of diverse algal groups in a wide range of aquatic and, eventually, terrestrial environments. Plastids have on multiple occasions al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
84
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(86 citation statements)
references
References 114 publications
1
84
0
1
Order By: Relevance
“…Plastids are widely known as light-dependent cellular powerhouse organelles supplying sugar through photosynthesis to the algal and plant cells [ 1 – 6 ]. However, research over the past decade has shown that plastids exist on a functional and evolutionary continuum that includes a variety of non-photosynthetically functioning organelles [ 7 , 8 , 11 21 ]. Nevertheless, the evolutionary transitions of the electron transport system and the branched pathways for the electron sink between photosynthetic and non-photosynthetic plastids have remained unclear.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plastids are widely known as light-dependent cellular powerhouse organelles supplying sugar through photosynthesis to the algal and plant cells [ 1 – 6 ]. However, research over the past decade has shown that plastids exist on a functional and evolutionary continuum that includes a variety of non-photosynthetically functioning organelles [ 7 , 8 , 11 21 ]. Nevertheless, the evolutionary transitions of the electron transport system and the branched pathways for the electron sink between photosynthetic and non-photosynthetic plastids have remained unclear.…”
Section: Resultsmentioning
confidence: 99%
“…It also retains the most reduced system of photosynthetic electron transport comprising only Fd and FNR [ 9 , 10 ]. However, recent investigations have greatly expanded the spectrum of known functions of remnant plastids in non-photosynthetic algal/plant lineages [ 11 19 ] and have been reviewed in recent papers [ 20 , 21 ]. For example, the non-photosynthetic diatom plastid in Nitzschia sp.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, from the data in hand we propose a modified model of chrysophyte plastid evolution, as follows ( Figure 5 ). The red alga-type plastid of photosynthetic chrysophytes stems from a secondary (or possibly) tertiary endosymbiotic event in an ancestor shared with other plastid-bearing stramenopiles (see Sibbald and Archibald, 2020 and references therein; Figure 5 , ①). Much later, after the diversification of chrysophytes, Spumella -like flagellates lost their photosynthesis-related genes on multiple occasions ( Figure 5 , ②, ③).…”
Section: Resultsmentioning
confidence: 99%
“…The loss of photosynthesis in autotrophic organisms containing primarily and secondarily derived plastids has occurred multiple times during the course of eukaryotic evolution ( Kim and Archibald, 2009 ; Hadariová et al., 2018 ; Maciszewski and Karnkowska, 2019 ; Sibbald and Archibald, 2020 ). Although the loss of most or all photosynthesis-related genes leads to a reduction in plastid genome size and complexity, most non-photosynthetic taxa retain a plastid genome.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the importance of this event, a variety of aspects of plastid evolution have long remained shrouded in mystery. In a review in Genome Biology and Evolution , Shannon Sibbald and John Archibald highlight emerging genome data in this field and provide new insight into plastid evolution ( Sibbald and Archibald 2020 ).…”
mentioning
confidence: 99%